CORPORATE REPUTATION AND THE PATH FROM CSR TO PROFIT IN CHINA'S FOOD COMPANIES - Azlan Ali; Xu Jiaqi (Journal of Artificial Intelligence and Digital Economy, 2024)
The financial success of a business is closely tied to its ability to meet its social responsibilities towards its stakeholders, who contribute valuable resources to the business. Corporate Social Responsibility (CSR) is the embodiment of corporate social behaviour, which has an impact on both a company's reputation and its performance. The study seeks to examine the influence of fulfilling corporate social responsibility (CSR) on financial success, with a focus on the mediating effect of company reputation. In order to accomplish this objective, this study focuses on examining publicly traded companies in China's food market. By utilizing both domestic and foreign theoretical study findings and practical exploration experiences on corporate social responsibility (CSR), business reputation, and financial performance. This study employs the literature review method to elucidate the theoretical foundation that supports the research and uncover the mechanism by which corporate performance is enhanced by the fulfilment of social responsibility by listed businesses in the food industry in China. And find the intermediary role of corporate reputation and investigates the mechanisms and pathways through which social responsibility and corporate reputation influence corporate performance. The findings will help to enhance the current understanding of the relationship between corporate social responsibility (CSR) and financial success. Additionally, it will offer valuable insights for future research and practical applications in this field..